2017
DOI: 10.1111/bjd.15078
|View full text |Cite
|
Sign up to set email alerts
|

T helper (Th)1, Th17 and Th2 imbalance in mesenchymal stem cells of adult patients with atopic dermatitis: at the origin of the problem

Abstract: The profile of MSCs obtained from patients with chronic AD retraces the Th1/Th17 cell environment observed in differentiated cells of chronic AD. This evidence could open a new scenario in the pathogenesis of AD, according to which the inflammatory process may involve MSCs early on.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 34 publications
5
60
0
Order By: Relevance
“…The level of secreted cytokines at baseline confirm the imbalance of Th1/17 versus the Th2 axis also observed in our previous studies [4,8,23]: MSCs from psoriatic patients secrete higher amounts of Th1/Th17 inflammatory molecules (IL-6, IL-12, IL-13, IL-17A, TGF-b, IFN-g, TNF-a and G-CSF) than MSCs from control subjects. Conversely, IL-2 is less secreted by PsO-MSCs than H-MSCs.…”
Section: Discussionsupporting
confidence: 88%
“…The level of secreted cytokines at baseline confirm the imbalance of Th1/17 versus the Th2 axis also observed in our previous studies [4,8,23]: MSCs from psoriatic patients secrete higher amounts of Th1/Th17 inflammatory molecules (IL-6, IL-12, IL-13, IL-17A, TGF-b, IFN-g, TNF-a and G-CSF) than MSCs from control subjects. Conversely, IL-2 is less secreted by PsO-MSCs than H-MSCs.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, psoriasis, a Th1-Th17-mediated disease [1], was found in 4% of our patients (10/253), a percentage which is similar to the psoriasis prevalence in general population, suggesting a possible overlap between Th1-Th17 and Th-2 pathways in AD, especially in adult-onset or persistent chronic forms as reported by a study conducted among Korean adults visiting health service centre in Seul [13]. Indeed, the importance of Th1-Th17 pathway in AD course is further supported by a very recent study which showed that the profile of Cutaneous Mesenchymal Stem Cells, obtained from patients suffering from chronic AD, retraces a Th1-Th17 environment [up-regulation of interleukin (IL)6, IL8, IL12, IL13, IL17A, IL17F, transforming growth factor-b, interferon-c, whereas Th2 chemokines such as IL2, IL4, IL5, and IL23A were down-regulated) [21].…”
Section: Discussionmentioning
confidence: 76%
“…According to the cytokines secreted, T helper cells (Th cells) can be classified into Th1, Th2 and Th17 . Keeping Th1/Th2/Th17 balance is key to maintain body immune and inflammatory homeostasis .…”
Section: Introductionmentioning
confidence: 99%